2014
DOI: 10.1089/ars.2013.5471
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Mechanosensitive Channels: Models for Studying Mechanosensory Transduction

Abstract: Significance: Sensations of touch and hearing are manifestations of mechanical contact and air pressure acting on touch receptors and hair cells of the inner ear, respectively. In bacteria, osmotic pressure exerts a significant mechanical force on their cellular membrane. Bacteria have evolved mechanosensitive (MS) channels to cope with excessive turgor pressure resulting from a hypo-osmotic shock. MS channel opening allows the expulsion of osmolytes and water, thereby restoring normal cellular turgor and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 161 publications
0
29
0
Order By: Relevance
“…A small-conductance mechano-sensitive channel (Saci_1914) had a log 2 -FC increase of 7.8 in the presence of full salt. Small-conductance mechano-sensitive channels open and close in response to stretching of the membrane, protecting the cell against osmotic shock (Martinac et al, 2014), and their role in archaea is well established (Kloda & Martinac, 2002).…”
Section: Rna Transcripts As a Response To Growth Without Sodium Or Pomentioning
confidence: 99%
“…A small-conductance mechano-sensitive channel (Saci_1914) had a log 2 -FC increase of 7.8 in the presence of full salt. Small-conductance mechano-sensitive channels open and close in response to stretching of the membrane, protecting the cell against osmotic shock (Martinac et al, 2014), and their role in archaea is well established (Kloda & Martinac, 2002).…”
Section: Rna Transcripts As a Response To Growth Without Sodium Or Pomentioning
confidence: 99%
“…Both MscS and MscL respond to extracellular osmotic challenges to prevent cell lysis (Booth, 2014; Martinac et al, 2014). In contrast the physiological role of TRAAK in mechanotransduction is not completely understood, but it is widely expressed in neurons and is involved in mechanical and thermal nociception in mice (Noël et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Homologs of MscS are found in nearly all bacterial species (Pivetti et al, 2003;Lai et al, 2013;Martinac et al, 2013), protozoa (Prole and Taylor, 2013), archaea (Palmieri et al, 2009), some fungi (Nakayama et al, 2012), and all plant genomes so far analyzed (Wilson et al, 2013) but have not been identified in animals. The region of sequence similarity between MscS and other members of the MscS superfamily is restricted to a relatively small portion of the protein that includes the pore-lining helix of MscS and ;100 amino acids of the upper cytoplasmic domain (Kloda and Martinac, 2002;Pivetti et al, 2003;Balleza and Gómez-Lagunas, 2009;Haswell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%